Enhancing Character Formation and Islamic Knowledge through Recitation Teaching at TPA Darussalam Negeri Ureng, Maluku Tengah, Indonesia - Fransina Latumahina; Mahudin Akbar Latupono; Made Alim Talaohu; Asmita Lukaraja; Anisa Kerubun (Universitas Muhammadiyah Sidoarjo, 2023)
This research article explores the implementation of a recitation teaching movement at TPA Darussalam Negeri Ureng in the Leihitu sub-district of Central Maluku, Indonesia. The study aims to foster empathy and concern for community issues while providing additional religious education to children in the region. The teaching methodology employed includes memorization techniques, focusing on Juz Amma and the Quran as well as understanding Quranic verses and stories. KKN students serve as assistant instructors, supporting the ustadzah in teaching recitation activities. The recitation classes take place daily from 14:00 to 16:00 WIT. The article outlines the steps involved in the implementation process, including the methods, techniques, and materials used. The results indicate that this initiative has positively influenced various aspects of the children's lives, such as increased Quranic reading and practice, improved public speaking skills during religious events, and enhanced discipline and respectful behavior in worship and social interactions. The findings suggest that recitation teaching at TPA Darussalam Negeri Ureng contributes to character formation and Islamic knowledge among the youth in the community. The implications of this research highlight the importance of incorporating such initiatives into educational programs to further promote moral values, Islamic teachings, and community engagement among young individuals. Highlight: Unique approach: The implementation of KKN at Darussalam Negeri Ureng TPA offers a distinctive approach to community development, focusing on religious education and character formation beyond formal schooling. Method and technique: The teaching methodology at TPA includes memorization and understanding of Quranic verses, fostering a deeper understanding of Islamic knowledge among children. Community involvement: The active participation of Ureng State KKN students in teaching recitation activities at TPA fosters community engagement and socialization opportunities for the children, creating a supportive learning environment. Keyword: KKN Implementation, Darussalam Negeri Ureng Al-Qur'an Study Place (TPA), Religious Education, Community Engagement, Character Formation